Which patients benefit specifically from short-term psychodynamic psychotherapy (STPP) for depression? Study protocol of a systematic review and meta-analysis of individual participant data. Issue 2 (20th February 2018) - Driessen, Ellen; Abbass, Allan A; Barber, Jacques P; Connolly Gibbons, Mary Beth; Dekker, Jack J M; Fokkema, Marjolein; Fonagy, Peter; Hollon, Steven D; Jansma, Elise P; de Maat, Saskia C M; Town, Joel M; Twisk, Jos W R; et al.
Abstract : Introduction: Short-term psychodynamic psychotherapy (STPP) is an empirically supported treatment that is often used to treat depression. However, it is largely unclear if certain subgroups of depressed patients can benefit specifically from this treatment method. We describe the protocol for a systematic review and meta-analysis of individual participant data (IPD) aimed at identifying predictors and moderators of STPP for depression efficacy. Method and analysis: We will conduct a systematic literature search in multiple bibliographic databases (PubMed, PsycINFO, Embase.com, Web of Science and Cochrane's Central Register of Controlled Trials), 'grey literature' databases (GLIN and UMI ProQuest) and a prospective trial register (http://www.controlled-trials.com ). We will include studies reporting (a) outcomes on standardised measures of (b) depressed (c) adult patients (d) receiving STPP. We will next invite the authors of these studies to share the participant-level data of their trials and combine these data to conduct IPD meta-analyses. The primary outcome for this study is post-treatment efficacy as assessed by a continuous depression measure. Potential predictors and moderators include all sociodemographic variables, clinical variables and psychological patient characteristics that are measured before the start of treatment and are assessed consistently across studies. One-stage IPD meta-analyses will be conducted using mixed-effects models. Ethics and dissemination: Institutional review board approval is not required for this study. We intend to submit reports of the outcomes of this study for publication to international peer-reviewed journals in the fields of psychiatry or clinical psychology. We also intend to present the outcomes at international scientific conferences aimed at psychotherapy researchers and clinicians. The findings of this study can have important clinical implications, as they can inform expectations of STPP efficacy for individual patients, and help to make an informed choice concerning the best treatment option for a given patient. PROSPERO registration number: CRD42017056029 .